Síntese e caracterização de ferritas de níquel dopadas com cobalto e efeito da substituição nas suas propriedades magnéticas - Rodrigues, Ádila Priscilla Gomes (2014)
The ferrite composition Ni1 - xCoxFe2O4 (0 ≤ x ≤ 0.75) were obtained by the method of microwave assisted synthesis and had their structural and magnetic properties evaluated due to the effect of the substitution of Ni by Co. The compounds were prepared: according to the concept of chemical propellants and heated in the microwave oven with power 7000kw. The synthesized material was characterized by absorption spectroscopy in the infrared (FTIR), Xray diffraction (XRD) using the Rietveld refinement, specific surface area (BET) , scanning electron microscopy (SEM) with aid of energy dispersive analysis (EDS) and magnetic measurements (MAV). The results obtained from these techniques confirmed the feasibility of the method of synthesis employed to obtain the desired spinel structure, the ferrite, nickel ferrite as for nickel doped with cobalt. The results from XRD refinement ally showed the formation of secondary phases concerning stages α - Fe2O3, FeO, (FeCo)O e Ni0. On the other hand, there is an increase in crystallite size with the increase of cobalt in systems, resulting in an increased crystallinity. The results showed that the BET systems showed a reduction in specific surface area with the increase of cobalt and from the SEM, the formation of irregular porous blocks and that the concentration of cobalt decreased the agglomerative state of the system. The magnetic ferrites studied showed different characteristics according to the amount of dopant used, ranging from a very soft magnetic material (easy magnetization and demagnetization ) - for the system without cobalt - a magnetic material with a little stiffer behavior - for systems containing cobalt. The values of the coercive field increased with the increasing growth of cobalt, and the values of saturation magnetization and remanence increased up to x = 0,25 and then reduced. The different magnetic characteristics presented by the systems according to the amount of dopant used, allows the use of these materials as intermediates magnetic